The effect of microwave treatment on the color changes and wettability of sembilang bamboo (Dendrocalamus giganteus Munro) - Davinsy, Rynaldo; Rahayu, Istie Sekartining (ULIN: Jurnal Hutan Tropis, 2024)
Bamboo has the potential to be a substitute for wood, although it is no exception that bamboo has many weaknesses. Bamboo is a plant with fast growth, short recycling times, and the potential to be used as structural and non-structural materials. Sembilang bamboo is a bamboo that has a large diameter and is commonly known as giant bamboo. Poor adhesive dispersion was a problem in previous studies, and the presence of discoloration due to important treatments was known. Heating using a microwave is a step in this research to solve the problems that occur. The research was carried out by measuring bamboo samples of a certain size, then the bamboo was scanned, and the wettability was measured initially and at the end of the test. Bamboo samples were heated in the microwave at a certain temperature of 60–75°C for 0.5–1 minute. The results of the 1 minute and 0.5 minute microwave treatment tests can increase wettability so that the spread becomes longer, with a small K value of 0.391. This is presumably because the contact angle is less than 90°. In addition, the treatment also had a small and moderate effect on the color differences that occurred.